Interaction of Hereditary Thrombophilia and Traditional Cardiovascular Risk Factors on the Risk of Arterial Thromboembolism: Pooled Analysis of Four Family Cohort Studies. (February 2016) - Mahmoodi, Bakhtawar K.; Veeger, Nic J.G.M.; Middeldorp, Saskia; Lijfering, Willem M.; Brouwer, Jan-Leendert P.; ten Berg, Jur; Hamulyák, Karly; Meijer, Karina
Abstract : Background—: Hereditary thrombophilia is associated with a slightly increased risk of arterial thromboembolism (ATE). Whether hereditary thrombophilia interacts with traditional cardiovascular risk factors on the risk of ATE has yet to be established. Methods and Results—: A total of 1891 individuals belonging to 4 family cohorts from the Netherlands were included in the analyses. Five hereditary thrombophilic defects, including factor V Leiden, prothrombin G20210A defect, and deficiencies of the natural anticoagulants (ie, antithrombin, protein C, and protein S), were assessed, and data on risk factors and previous ATE were collected. Thrombophilia was associated with elevated risk of ATE (hazard ratio =1.74, 95% confidence interval, 1.18–2.58; P =0.005). Overall, the association of thrombophilia with ATE tended to be stronger in the presence of traditional cardiovascular risk factors, especially the synergistic effect of thrombophilia with diabetes mellitus was striking (hazard ratio of thrombophilia–ATE association was 1.41 in nondiabetics versus 8.11 in diabetics). Moreover, the association of thrombophilia with ATE tended to be stronger in females and before the age of 55 years as compared with males and individuals >55 years of age, respectively. Conclusions—: Thrombophilia is associated with ATE. This association may be stronger in the presence of traditional cardiovascular risk factors in particular in individuals with diabetes mellitus. Future studies on thrombophilia–ATE risk should focus on high-risk populations with high prevalence of traditional cardiovascular risk factors. Abstract : Supplemental Digital Content is available in the text.